LANGUAGE FUNCTION USED BY MARIO TEGUH IN MARIO TEGUH GOLDEN WAYS SHOW - HIDAYAT, MUHAMMAD HILMAN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Hidayat, Muhammad Hilman. 2013. Language Function Used by Mario Teguhin Mario Teguh Golden Ways show. Study Program of English, Department ofLanguages and Literature, Faculty of Cultural Studies, Universitas Brawijaya.Supervisor: Lalu Merdi; Co-supervisor: Istiqomah Wulandari.Keywords: Language functions, Mario Teguh Golden Ways video.Language is very important for human life. People use it forcommunication in delivering idea, feeling, messages, etc. In society, language has some aspects. One of the aspects that can be stated of language is language function. The researcher conducts a research about language functions that are used by Mario Teguh in Mario Teguh Golden Ways show by using Jakobson and Hymes’ theory. This research focuses on two problems: (1) What elements of communication are used in Mario Teguh Golden Ways show (2) What language functions are used by Mario Teguh.This research uses qualitative approach in document analysis to describe the language functions used by Mario Teguh in Mario Teguh Golden Ways show. The data are transcribed utterances produced by Mario Teguh taken from Mario Teguh Golden Ways entitled Mengatasi Rasa Takut Gagal video which is uploaded on Youtube website.This research reveals that all seven elements of communication are found in Mario Teguh Golden Ways show entitled Mengatasi Rasa Takut Gagal namelyaddresser, addressee, channel, message form, topic, code, and setting. This study also reveals six out of seven language functions used by Mario Teguh. They are emotive function, directive function, phatic function, poetic function, referential function and metalinguistic function. Referential function is the most used by Mario Teguh. He needs to use this function because motivation requires a lot of information to be informed to the audience during the speech. Furthermore, this research shows that there is a combination among the language functions. It means, one utterance does not only bring one function but also two or three functions at once. In short, elements of communication and language function should be seen from the context in a certain condition and situation.The researcher hopes that this research can contribute a better and deeperunderstanding about language function. He suggests the next researchersespecially English Department students conduct the research with differentobjects and theories of language function since this research did not cover allaspects of language function.